2021
DOI: 10.1101/2021.04.10.21255250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Standardized and optimized preservation, extraction and quantification techniques for detection of fecal SARS-CoV-2 RNA

Abstract: COVID-19 patients shed SARS-CoV-2 viral RNA in their stool, sometimes well after they have cleared their respiratory infection. This feature of the disease may be significant for patient health, epidemiology, and diagnosis. However, to date, methods to preserve stool samples from COVID patients, and to extract and quantify viral RNA concentration have yet to be optimized. We sought to meet this urgent need by developing and benchmarking a standardized protocol for the fecal detection of SARS-CoV-2 RNA. We test… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…To prevent this, several methods including different stabilization buffers have been developed in the recent years [38,40,41]. In line with the results reported by Roesch et al [42], we found a higher amount of Enterobacteriaceae in samples stored at RT for 3 -5 days, when compared to the same sample when directly frozen.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To prevent this, several methods including different stabilization buffers have been developed in the recent years [38,40,41]. In line with the results reported by Roesch et al [42], we found a higher amount of Enterobacteriaceae in samples stored at RT for 3 -5 days, when compared to the same sample when directly frozen.…”
Section: Discussionsupporting
confidence: 91%
“…Collecting and transporting samples at room temperature however promotes the overgrowth of facultative anaerobes and potential degradation of nucleic acids by breakdown of strict anaerobes. To prevent this, several methods including different stabilization buffers have been developed in the recent years [38, 40, 41]. In line with the results reported by Roesch et al [42], we found a higher amount of Enterobacteriaceae in samples stored at RT for 3 – 5 days, when compared to the same sample when directly frozen.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, noninvasive sampling of faecal droppings, for example, can be very difficult to collect fresh enough from cryptic and/or evasive animals and such specimens do not necessarily allow satisfactory detection of all pathogens. Furthermore, these samples often represent difficult media for pathogen detection due to nucleic acid or protein degradation and also because they contain inhibitors of the extraction or amplification reagents required for molecular analysis (Natarajan et al, 2021 ; Sarabia et al, 2020 ). New complementary approaches are therefore needed for monitoring and detecting pathogens in wildlife.…”
Section: Introductionmentioning
confidence: 99%